Hemostatic Action of OC-108, a Novel Agent for Hemorrhoids, Is Associated With Regional Blood Flow Arrest Induced by Acute Inflammation - Takashi Ono; Haruto Nakagawa; Atsushi Fukunari; Toshio Hashimoto; Hirotsugu Komatsu (Elsevier, 2006)
Clinically, hemorrhoidal bleeding and prolapse disappeared immediately after injection of the sclerosing agent OC-108 into submucosa of hemorrhoids. The aim of this study was to elucidate the mechanism of action responsible for the immediate hemostatic effect of OC-108 using anesthetized rats. Subcutaneous injection of OC-108 in rats decreased blood flow at the injection site within 5 min. Aluminum potassium sulfate, one of the main ingredients of OC-108, reduced the skin blood flow. However, tannic acid, another main ingredient, did not. By perfusion of OC-108 on the mesenteric surface, microcirculatory blood flow was arrested without remarkable change in blood vessel diameter, accompanied by increased vascular permeability and venous hematocrit. These results indicate that OC-108 induces regional blood flow arrest with rapid onset, this effect being attributed to the action of aluminum potassium sulfate, and that hemoconcentration due to increased vascular permeability (plasma extravasation), an acute inflammatory reaction, is involved in the mechanisms of the immediate hemostatic action of OC-108. Keywords:: OC-108, hemorrhoidal bleeding, blood flow arrest, vascular permeability, hemoconcentration